The Communist Manifesto - A Hnuder and Fifty Years After - Pascual, Frank (Kasarinlan: Philippine Journal of Third World Studies, 2009)
For more than 150 years, the Communist Manifesto of Karl Marx and Friedrich Engels has provided an analysis of the evolution of bourgeois society from the ruins of feudal society, an outline of the inherent contradictions of the capitalist system, and a prediction of the inevitable capitalist crisis leading to the system’s eventual defeat. The Manifesto has projected the triumph of socialism and the proletariat’s coming to power through a socialist revolution. Its analysis has been borne out by the recurring crisis of capitalism as well as the experience of the proletariat in its struggle for socialism in the intervening 150 years since it was written. It continues to be borne out by the most recent economic and political developments. Moreover, it continues to illumine the path of the proletariat in its struggle for socialism. The process described in the Manifesto is ongoing. Hence, the document is as applicable today as it was 150 years ago.